Ex vivo and in vitro methods as a platform for studying anthropogenic effects on marine mammals: four challenges and how to meet them - Vazquez, Juan Manuel; Khudyakov, Jane I.; Madelaire, Carla B.; Godard-Codding, Céline A.; Routti, Heli; Lam, Emily K.; Piotrowski, Elizabeth R.; Merrill, Greg B.; Wisse, Jillian H.; Allen, Kaitlin N.; Conner, Justin; Blévin, Pierre; et al. (Frontiers in Marine Science, 2024)
Marine mammals are integral to global biodiversity and marine health through their roles in coastal, benthic, and pelagic ecosystems. Marine mammals face escalating threats from climate change, pollution, and human activities, which perturb their oceanic environment. The diverse biology and extreme adaptations evolved by marine mammals make them important study subjects for understanding anthropogenic pressures on marine ecosystems. However, ethical and logistical constraints restrict the tractability of experimental research with live marine mammals. Additionally, studies on the effects of changing ocean environments are further complicated by intricate gene-environment interactions across populations and species. These obstacles can be overcome with a comprehensive strategy that involves a systems-level approach integrating genotype to phenotype using rigorously defined experimental conditions in vitro and ex vivo. A thorough analysis of the interactions between the genetics of marine mammals and their exposure to anthropogenic pressures will enable robust predictions about how global environmental changes will affect their health and populations. In this perspective, we discuss four challenges of implementing such non-invasive approaches across scientific fields and international borders: 1) practical and ethical limitations of in vivo experimentation with marine mammals, 2) accessibility to relevant tissue samples and cell cultures; 3) open access to harmonized methods and datasets and 4) ethical and equitable research practices. Successful implementation of the proposed approach has the potential impact to inspire new solutions and strategies for marine conservation.